The development of achievement emotions and coping/emotion regulation from primary to secondary school. (April 2016) - Vierhaus, Marc; Lohaus, Arnold; Wild, Elke
Abstract: This study reports on the development of achievement emotions and coping/emotion regulation in primary to secondary school-aged children and adolescents. Based on two longitudinal cohorts (Grades 2–5; Grades 4–7), latent growth models were used to analyze the development of achievement emotions and coping strategies separately as well as simultaneously. The results show that enjoyment decreases across grades, whereas boredom increases, with substantial changes between Grade 5 and Grade 7. Consistently, the development of enjoyment is positively associated with the development of problem-focused coping and palliative emotion regulation, whereas the development of boredom is positively associated with the development of avoidant coping and anger-related emotion regulation. Moreover, the relation between problem-focused coping and boredom, as well as between avoidant coping and enjoyment, depends on the age group. The results are discussed regarding the organization of learning environments in classes to prevent unfavorable developmental patterns of achievement emotions. Graphical abstract: Highlights: Particularly between grade 5 and 7, enjoyment decreases while boredom increases. Both emotions show specific developmental relations to coping/emotion regulation. Some relations to achievement emotions and coping/emotion regulation depend on age. Results may help to prevent inimical developmental patterns of achievement emotions. Prevention should focus on the organization of learning environments in classes.